Scrutinizing pharmacological efficiency for Acacia auriculiformis by experimental and computational approach - Shafinaz Nur; Md. Mohotasin Hossain; Nadia Islam; Abu Montakim Tareq; Nujhat Binte Hanif; Riniara Khatun; Mohammed Abu Sayeed (SpringerOpen, 2021)
Abstract Background The study sought to investigate the biological efficacy of methanol leave extract of Acacia auriculiformis (MEAA) via in vitro, in vivo, in silico approaches. The in vitro cytotoxicity was evaluated through brine shrimp lethality assay, and anti-inflammatory activity was determined by membrane stabilisation and protein denaturation methods (BSA and egg albumin). The in vivo antipyretic activity was examined via Brewer's yeast induced pyrexia model. Results A. auriculiformis extract unveiled moderate cytotoxicity with significant anti-inflammatory efficacy (p < 0.001) compared to standard drug. This extract also exhibited dose-dependent time of paralysis and death for the worm (p < 0.001) in the anthelmintic test which was directly proportional to employed concentrations. A notable percentage of clot lysis effect (36.42 ± 1.95%, p < 0.001) was also observed for MEAA in human blood compared to control. However, this extract significantly (p < 0.05) reduced fever in a dose-dependent manner during the antipyretic experiment. Besides, in computer-aided investigations, two compounds (2,4-ditert-butylphenol and 3-hydroxy-β-damascone) revealed the best binding interaction with six proteins for cytotoxicity, inflammation, helminthic, thrombolytic and pyretic effect. Moreover, these two compounds satisfy Lipinski's 'Rule of Five' and revealed drug-likeness profiles in the toxicological study. Conclusions These findings disclosed that methanol leaves extract of A. auriculiformis might be a potent source for anti-inflammatory, anti-helminthic, thrombolytic and antipyretic agents.